A Two‐Step Modified Sequential Deposition Method‐based Pb‐Free (CH3NH3)3Sb2I9 Perovskite with Improved Open Circuit Voltage and Performance. Issue 4 (11th February 2020) - Ahmad, Khursheed; Kumar, Praveen; Mobin, Shaikh M.
Abstract: In the last decade, photovoltaic devices employing lead halide perovskites as light absorber have pulled the attention of researchers due to their outstanding performance. However, the lead halide perovskite based photovoltaic devices suffering from the toxicity of lead (Pb) and lower stability in air. Herein, we have replaced Pb with less toxic antimony (Sb) to prepare air stable and Pb‐free perovskite light absorber. Moreover, we have developed a two‐step procedure to prepare the high quality films of perovskite light absorber with device architecture of FTO/CL‐TiO2 /m‐TiO2 /MASbI/HTM/Au. This fabricated Pb‐free perovskite solar cell device prepared with two‐step procedure shows good performance with remarkably good open circuit voltage of 740 mV. Abstract : Easy as 1–2 ! A two‐step modified sequential deposition method is employed to prepare the high quality thin film of a Pb‐free perovskite, MASbI, for solar cell applications.